Probabilistic methods in discontinuities for the stability of road tunnels and half-tunnels of Karkatera-Abancay - Cárdenas_Catalán, José A. (2022)
For decades, rock structures were designed based on empirical methods, based on professional experience, support systems tended to be overestimated with the consequent increase in costs, without giving interest to the intrinsic resistance of the rock and applied to Similar cases. The development of the study of Rock Mechanics has reached high levels that have contributed to solving complex problems in rock masses of varied geomechanical conditions, allowing the construction of extensive works in low resistance massifs such as long underground tunnels, underground constructions, food pantries. , underground shelters among others, to take advantage of underground space, especially in countries with high population density. The objective in the Road Tunnels is to seek adequate support for their stability, through a probabilistic study. In the excavation of the Karkatera tunnels, the use of dosed explosives allowed the works to be carried out in a short time, an attempt was made to cause the least damage to the surrounding rock masses with regular and controlled cuts that reduced the need for reinforcements, but even so The rock mass has its behavior governed by discontinuities characterized by conditions such as orientation, persistence, spacing, roughness, etc. that define the degree of fracturing of the rock mass and its resistance to cutting. The present investigation studied the geometric parameters of the families of discontinuities using probabilistic methods to evaluate the probability of rupture of the structures in these civil works with positive results, which allows proposing adequate stabilization methods.